1969
DOI: 10.1172/jci105970
|View full text |Cite
|
Sign up to set email alerts
|

Peptide hydrolase activities of the mucosa of human small intestine

Abstract: A B S T R A C T Few studies have been published on peptide hydrolase activities of human small intestine mucosa. We developed methods to screen tissue extracts for such enzymes and to quantitate hydrolase activities for dipeptides containing the aromatic amino acid L-phenylalanine. The screening procedure indicated glyCyl-L-proline hydrolase activity was reduced in biopsy specimens from patients with flattened intestinal mucosa. To explore this further, we established optimal assay conditions for hydrolaseBiop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

1971
1971
1983
1983

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(19 citation statements)
references
References 22 publications
1
17
0
1
Order By: Relevance
“…In addition, the present data, as will be discussed later, strongly suggest that glycylleucine is also absorbed in this fashion in the human intestine. The failure to demonstrate the presence of the former dipeptide in plasma in the present study may have been due to the much greater peptide hydrolase activity against glycylleucine than against glycylglycine in tissues such as intestine (12,13). All available findings considered, this transport phenomenon appears not only to encompass the above two dipeptides, but also to apply to a substantial range of dipeptides (20)(21)(22).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…In addition, the present data, as will be discussed later, strongly suggest that glycylleucine is also absorbed in this fashion in the human intestine. The failure to demonstrate the presence of the former dipeptide in plasma in the present study may have been due to the much greater peptide hydrolase activity against glycylleucine than against glycylglycine in tissues such as intestine (12,13). All available findings considered, this transport phenomenon appears not only to encompass the above two dipeptides, but also to apply to a substantial range of dipeptides (20)(21)(22).…”
Section: Discussionmentioning
confidence: 53%
“…The selection of these two dipeptides offered an opportunity to examine the influence of rapid and slow hydrolyses of dipeptides by the mucosal enzymes on their relative rates of disappearance in the intestine. Previous studies had shown that, comparatively, glycylleucine is an excellent and glycylglycine is a poor substrate for the human mucosal peptide hydrolases (12,13). Furthermore, microvillous membrane isolated from hamster intestinal epithelial cells demonstrated considerably lower hydrolytic activity against glycylglycine than against other dipeptides (14).…”
Section: Introductionmentioning
confidence: 98%
“…3 Other substrates used were L-leucyl-p-naphthylamide hydrochloride2 and L-leucinamide hydrochloride. 2 Trypsin,' chymotrypsin,' papain,5 Triton X-100,6 Na deoxycholate,' Na glycodeoxycholate,' Na glycocholate,' and Enzite-papain 8 were used to release peptide hydrolases from the brush border membrane. Hydrolyzed starch was used for the preparation of the gel used in electrophoresis.…”
Section: Methodsmentioning
confidence: 99%
“…These enzymes have been reported to occur both in brush border membranes and in the soluble cytoplasmic fraction (1)(2)(3)(4)(5)(6). Although data regarding the quantitative distribution of peptide hydrolases in these fractions are lacking, it has been reported that the brush border membrane contains less dipeptide hydrolase activity than the soluble cytosol fraction, while tripeptide hydrolase activity is much more active in the former (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Since the Matheson and Tattrie method gave high blank values when these dipeptides were used as substrates, a one-step modification' of previously reported L-amino acid oxidase methods was used for assays of peptide hydrolase activities (16,22,23). Each dipeptide was dissolved in 0.5 ml 50 mM Tris-HCl buffer, pH 8.0.…”
Section: Experiments Imentioning
confidence: 99%